FORMING AN EFFECTIVE MECHANISM OF SOCIOPOLITICAL STABILITY IN THE NORTHERN CAUCASUS - RESHIEV, Sulaiman (CENTRAL ASIA AND THE CAUCASUS, 2009)
At the current stage of Russia’s development it is extremely important to create an effective mechanism of sociopolitical stability in the Southern Federal Okrug (SFO). The creation (drawing up) and continuous functioning of this mechanism is a necessary prerequisite for the sustainable economic development of the Russian South (and of all the territories that belong to it), as well as the country as a whole.The federal government is becoming increasingly aware that new transportation projects can be only implemented in the Caspian region if military and political security both here and throughout the Northern Caucasus is ensured. In turn, the new transit systems in the Caspian are not only economically advantageous projects for Russia, but also an effective way to protect its geopolitical interests in the Caspian-Black Sea region.Today Russia can only retain its position in the greater Caspian-Black Sea region by pooling its military and political resources and conducting an extensive regional socioeconomic policy in the problematic territories of the SFO. Without this it will be impossible to achieve sociopolitical stability in the key regions of the Northern Caucasus, including attract sufficient investments, particularly foreign, and carry out large-scale transit projects there.1In addition, regional researchers are concerned that most of the population and public organizations in the SFO are absolutely loyal to the government and only a small minority is engaged in constructive opposition to the regional bureaucrats.2The public organizations that have merged with the government are mainly engaged in justifying and legitimizing the existing social order with deliberate disregard of the current problems, such as the flagrant social injustice and corruption. Today, this state of society and public organizations in the SFO is arousing justified concern among many independent regional researchers, since social injustice and corruption will only lead to sociopolitical conflict in the future.